Sticky stock market analysts - Ibrahim Filiz; Jan René Judek; Marco Lorenz; Markus Spiwoks (Journal of Risk and Financial Management, 2021)
Technological progress in recent years has made new methods available for making forecasts in a variety of areas. We examine the success of ex-ante stock market forecasts of three major stock market indices, i.e., the German Stock Market Index (DAX), the Dow Jones Industrial Index (DJI), and the Euro Stoxx 50 (SX5E). We test whether the forecasts prove true when they reach their effective dates and are therefore suitable for active investment strategies. We revive the thoughts of the American sociologist William Fielding Ogburn, who argues that forecasters consistently underestimate the variability of the future. In addition, we draw on some contemporary measures of forecast quality (prediction-realization diagram, test of unbiasedness, and Diebold-Mariano test). We reveal that (a) unusual events are underrepresented in the forecasts, (b) the dispersion of the forecasts lags behind that of the actual events, (c) the slope of the regression lines in the prediction-realization diagram is <1, (d) the forecasts are highly biased, and (e) the quality of the forecasts is not significantly better than that of näive forecasts. The overall behavior of the forecasters can be described as 'sticky' because their forecasts adhere too strongly to long-term trends in the indices and are thus characterized by conservatism.
Keywords: D83; D84; D91; G17; G41; 330; stock market forecasting; forecasting bias; variability of reality; conservatism of predictors